FUNGSI NOTARIS DALAM PENGHAPUSAN JAMINAN FIDUSIA SECARA ELEKTRONIK - Felisa, Aulia (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
The role o notary in the registration of fiduciary security to the secrecy of electronic securities fiduciary must be great, considering its participation from the very beginning before entering to register electronically until the time to register electronically until printing the fiduciary guarantee registration of course the legal certainty must be guaranteed either for fiduciary, fiduciary, or third party beneficiaries. Law No. 2 of 2014 concering the amandement to law No. 30 of 2004 concering the positionof a notary public and in the notary code of ethicsis not is not stipulated on the obligation of notary to carry out the blowing of the online fiduciary but the special acces given by the website of the directorate general of general law administration to the notary in the implementation of electronic fiduciary and electronic registration and deletion so that the notary can be concluded as the executor of fiduciary electronic registration and elimination.